(untitled) (Journal for Studies in Humanities and Social Sciences, 2019)
Fears about the imminent death of the print newspaper in the face of the ongoing digital revolution have been widespread for some time. But with miniaturized media tools and hand-held, internet-ready communication technologies offering unlimited on-the-go access to the news via multiple online platforms, prognostications to the effect that the hard copy newspaper may go extinct in the nearest future seem no more an idle speculation. Indeed, print media financiers, publishers, editors, and practitioners have not hidden their concern about the drastic effects of technology. This study comes on the heels of the widespread speculations that the emergence of digital media gadgets that enable online news access would deplete the economic viability of print newspaper houses by pushing news readers online. The situation became increasingly worrisome when some emerging scholarship reported that younger newspaper readers were abandoning the print copy newspaper for electronic and online news sources, which they believed offered greater ease and convenience. A survey (n=431) of respondents drawn from mass communication educators, practicing journalists and civil servants in Akwa Ibom State, Nigeria. Results showed that though the industry faces a significant economic decline, predictions that convergent, digital technology will compel readers to completely abandon print newspapers for digital news sources are not yet a reality, even though print’s business model is seriously strained. Survival strategies already adopted include cover price increase, headlines-online-details-in -print, collapse and merger of beats, downward review in wage bill/pay cuts and print run cuts. The study recommends that publishers and editors invent creative and engaging print contents and other strategies such as inserting interactive DVDs in some of their print issues, as had been experimented at some point. Results could be tremendous where such newspaper contents also focus primarily on their immediate surroundings, giving local readers exactly what they want – such news stories that are either not readily available on the web or are routinely overlooked by the mainstream media.